Pyrite assisted peroxymonosulfate sludge conditioning: uncover triclosan transformation during treatment - Liang, Jialin (2022)
Waste activated sludge (WAS) dewatering is a crucial process for sludge treatment and disposal. In this study, we proposed a novel pyrite (FeS2) and peroxymonosulfate (PMS) treatment to improve WAS dewaterability. Micropollutants are commonly enriched in the sludge. It is not clear if the micropollutants remain in the sludge during the conditioning. Triclosan (TCS) as a widely used bactericide often presents in the WAS, thus was chosen as a target micropollutant. Pyrite + PMS treatment could simultaneously enhance WAS dewaterability and TCS removal with low cost and high benefit. Under the optimal conditions, the specific resistance of filtration (SRF) and capillary suction time (CST) were reduced by 84.60% and 74.91%, respectively. Meanwhile, the TCS removal efficiency was 34.08% with four transformation products identified. During the pyrite + PMS process, sulfate radicals and hydroxyl radicals were generated and strong flocculation was induced by iron. These two processes significantly reduced the sticky biopolymers, hydrophilic functional groups, and hydrophilic protein molecular structure of extracellular polymeric substances (EPS), leading to the release of bound water and TCS. Collectively, the pyrite + PMS treatment is a promising alternative for simultaneous enhancement of WAS dewatering and micropollutants removal, which is beneficial to the downstream treatment.